Measures and effects of sick leave in Croatian catering industry - a review of productivity - Maškarin Ribarić, Helga (Oeconomica Jadertina, 2019)
In this paper, sick leave as a form of absenteeism is observed in the context of its negative impact on business results, with special emphasis on productivity, at the level of the overall economy and catering industry in particular as a key part of tourism that largely “drives” the entire Croatian economy. For this purpose, data on sick leave at EU and Croatia level were analysed and compared, whereas data for catering were analysed separately within the Croatian economy. The productivity losses due to sick leave for the Croatian economy were estimated using the HCA method and a comparison of the sick leave effects on Gross Value Added (GVA) between the hospitality and the overall Croatian economy was performed. The results of the analysis indicate a great negative impact of the sick leave on the achieved productivity (1.276% GVA of the Republic of Croatia), but also a significantly more favourable situation in the catering industry than the overall average for Croatia.